Sistem Kendali dan Pemantauan Ketinggian Air pada Tangki Berbasis Sensor Ultrasonik - Alawiah, Amelia; Al Tahtawi, Adnan Rafi (Puslitbang Kopertip Indonesia, 2017)
Control and monitoring systems of the water level tank is one of electrical, computer instrumentation that needed in industrial process. This paper presents control and monitoring systems of water level in a tank based on ultrasonic sensor. The ultrasonic sensor is a device that can measure the distance of an object by using ultrasonic wave deflection. The control system is designed using relay as a switch which is controlled by a microcontroller with hysteresis control law. For monitoring and measurement data, the interface device is also designed using the Processing software in form of graphic, bar chart, pump state, and charging/discharging duration. Testing result shows that the ultrasonic sensor that used able to measure water level of 5 cm to 25 cm with error measurement 4.93%. A hysteresis control system that designed can produce output responses according to the setpoint value without generating relay’s chattering. As an addition, monitoring system of water level can be displayed in the form of a software interface on the Processing interactively.